Acute on Chronic Pancreatitis Causing a Highway to the Colon with Subsequent Road Closure: Pancreatic Colonic Fistula Presenting as a Large Bowel Obstruction Treated with Pancreatic Duct Stenting - Justin Cochrane; Greg Schlepp (Case Reports in Gastrointestinal Medicine)
Context. Colonic complications associated with acute pancreatitis have a low incidence but carry an increased risk of mortality with delayed diagnosis and treatment. Pancreatic colonic fistula is most commonly associated with walled off pancreatic necrosis or abscess formation and rarely forms spontaneously. Classic clinical manifestations for pancreatic colonic fistula include diarrhea, hematochezia, and fever. Uncommonly pancreatic colonic fistula presents as large bowel obstruction. Case. We report a case of a woman with a history of recurrent episodes of acute pancreatitis who presented with large bowel obstruction secondary to pancreatic colonic fistula. Resolution of large bowel obstruction and pancreatic colonic fistula was achieved with pancreatic duct stenting. Conclusion. Pancreatic colonic fistula can present as large bowel obstruction. Patients with resolved acute pancreatitis who have radiographic evidence of splenic flexure obstruction, but without evidence of mechanical obstruction on colonoscopy, should be considered for ERCP to evaluate for PCF. PCF not associated with walled off pancreatic necrosis or peritoneal abscess can be treated conservatively with pancreatic duct stenting.